2009
DOI: 10.1021/es803268b
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for strong adsorption of tetracycline to carbon nanotubes: A comparative study using activated carbon and graphite as adsorbents

Abstract: Significant concerns have been raised over the presence of antibiotics including tetracyclines in aquatic environments. We herein studied single-walled carbon nanotubes (SWNT) and multi-walled carbon nanotubes (MWNT) as potential effective adsorbents for removal of tetracycline from aqueous solution. In comparison, a nonpolar adsorbate, naphthalene, and two other carbonaceous adsorbents, pulverized activated carbon (AC) and nonporous graphite, were used. The observed adsorbent-to-solution distribution coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
352
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 712 publications
(366 citation statements)
references
References 43 publications
10
352
3
1
Order By: Relevance
“…Thus, the ring current-induced upfield chemical shifts of 1 H NMR can serve as a strong evidence for face to face complexation of the probed molecule with aromatic structures. In previous studies, the observed 1 H/ 13 C NMR upfield chemical shifts have been used to support -EDA complexation between -electronacceptor compounds and PAHs (-electron-donors) [32]. In this study, prominent 1 HNM upfield shifts are observed for Nor + in mixtures with PAHs (-electron-donors).…”
Section: H Nmr Studiesmentioning
confidence: 59%
“…Thus, the ring current-induced upfield chemical shifts of 1 H NMR can serve as a strong evidence for face to face complexation of the probed molecule with aromatic structures. In previous studies, the observed 1 H/ 13 C NMR upfield chemical shifts have been used to support -EDA complexation between -electronacceptor compounds and PAHs (-electron-donors) [32]. In this study, prominent 1 HNM upfield shifts are observed for Nor + in mixtures with PAHs (-electron-donors).…”
Section: H Nmr Studiesmentioning
confidence: 59%
“…Among these methods, adsorption remains attractive because of its advantages of easy operation, energy savings and high removal capacity. Many adsorbents have been used to adsorb antibiotics or heavy metals from water separately, but fewer were used to remove them together (Figueroa et al, 2004;Ge et al, 2012;Ji et al, 2009;Oh et al, 2007;Sassman and Lee, 2005;Vu et al, 2010;Yang and Jiang, 2014;Hasan et al, 2013). In recent years, the cosorption of antibiotics and heavy metals from water by some adsorbents has been attracting increasing concern due to the realistic demands (Kang et al, 2010;Ling et al, 2013;Wang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, residues of TCs discharged from municipal wastewater treatment plants (WWTPs) and agricultural runoff are frequently detected in sewage, agricultural wastewater, surface water, groundwater, and even drinking water [5e7]. Exposures to low-level antibiotics in the environment have raised significant concerns of the toxic effect, as well as the transfer and spread of antibiotic resistant genes among microorganisms [7]. As stated by the World Health Organization, the increasing emergence of antibiotic resistance in human pathogens is a special concern, not only for treating infectious disease, but also for other pathologies in which antibiotic prophylaxis is needed for avoiding associated infections [8].…”
Section: Introductionmentioning
confidence: 99%